THE MORPHOLOGY OF THE LYMPH NODES IN INTRAUTERINELY ACQUIRED IMMUNODEFICIENCY IN CHILDREN WHO DIED FROM NEONATAL SEPSIS - Allaberganov, AlD.Sh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To identify morphological and morphometric changes in the lymph nodes in immunodeficiencies acquired in the prenatal and postnatal periods in children who died from neonatal sepsis. Material and Methods: Paratracheal and mesenteric lymph nodes taken during autopsy in 28 neonatal neonatal neonatal infants who underwent postmortem diagnosis of thyroid and postnatal immunodeficiency were taken during autopsy. Results: In case of intrauterinely acquired immunodeficiency, the main morphofunctional zones of the peripheral organs of immunogenesis are immature, hypoplastic due to underpopulation with lymphocytes. When secondary immunodeficiencies in the lymph nodes, changes occur depending on damage to the cellular or humoral immunity in the form of emptying the corresponding structural and functional areas, replacing them with reticular and connective tissue, as well as the absence of activation of lymphocytes and light reproduction centers. Conclusions: In neonatal neonatal deaths, secondary immunodeficiency’s manifest themselves in two forms: intrauterinely acquired and acquired in the early postnatal period. In the latter case, the main morphofunctional zones of the peripheral organs of immunogenesis are immature, hypoplastic due to underpopulation of lymphocytes.